PROSPECTIVE CLINICAL STUDY TO ASSESS THE SAFETY AND EFFICACY OF DRAVANTI BEEJ LEPA (LOCAL APPLICATION OF CROTON TIGLIUM) IN INDRALUPTA W. S. R. TO ALOPECIA AREATA - Thapliyal, Aprana Pankaj; Denge, Kalpana (International Journal of Research -GRANTHAALAYAH, 2018)
Indralupta (Alopecia Areata) is not life threatening disorder but it definitely affects the quality of life like impairing psychological well-being thus affecting mental and social status of person due to bald patch. It is characterized by smooth, circumscribed bald patch on the hair bearing area. The risk of allopathic treatment outweighs their benefits. Indralupta is considered under Kshudraroga by most of the authors of classical Ayurvedic texts. Safety and efficacy of Dravanti beeja lepa in regeneration of hair in Indralupta is assessed through present study. Prospective open randomized single-arm clinical trial was carried out on 30 patients showing classical symptoms of Indralupta. A Skin patch test has been done prior to apply the lepa for safety assessment. The Dravanti beeja lepa was given for local application twice a day over a period of 28 day. Indralupta was found to be more prevelant in males. Intake of Amla, Katu and lavana Rasa, non-vegetarian diet, stress factor and use of cosmetics could be considered as etiological factor of Indralupta. On regular use of Dravanti beeja lepa, regeneration of hair was also observed to significant level. Thus, Dravanti beeja lepa proved its safety and efficacy for topical application.